Penerapan Model Pembelajaran Contextual Teaching And Learning (CTL) Untuk Meningkatkan Pemahaman Materi Pasar Valuta Asing Pada Mata Kuliah Ekonomi Internasional 2 (Studi Mahasiswa Semester 5 Jurusan Ekonomi Pembangunan Fakultas Ekonomi UMSU) - Sri Endang Rahayu; Hastina Febriaty (JURNAL ILMIAH MANAJEMEN & BISNIS, 2016)
Based on the test results, there is increasing student’s understanding of the material implementation of IS-LM model in each cycle. The average value in the first cycle for the fourth semester / A / IESP reached 76.16 and the second cycle is 91.88. Mastery learning in the first cycle is 57.1% and the second cycle is 98.22%. The average value in the first cycle for fourth semester / B / IESP reached 76.25 and the second cycle is 97.95. Mastery learning in the first cycle is 54.5% and the second cycle is 97.73%. Increased understanding of the students followed by increased activity.The conclusion of this study is the student's understanding increased with applied learning model CTL in the 4th semester student majoring in economics faculty UMSU economic development. Researchers suggest that professors use in the CTL learning model learning course material application of IS-LM model in macroeconomic 2 courses and lecturers should earnestly to guide students in learning.Keywords :      Understanding of material application IS-LM model, Contextual Teaching and Learning